Latitudinal Range Extension of Indian Wild Ass (Equus hemionus Khur) in Gujarat - Western India - Parasharya, Dishant; Teli, Janki (Indian Forester, 2015)
The Wild ass (Equus hemionus khur) is protected under wildlife protection act and has been declared under schedule I and restricted to the parts of Gujarat, mainly in the protected areas (PA) of Wild ass Sanctuary and its fringes. However the number of wild ass has gone beyond the carrying capacity of the existing protected area. Till date most of the studies of the species are restricted to its status in and around the protected area. Except one publication, there are no reports of the species migrating to the lower latitudes and almost 100 km from the Protected Area. The observations on the species were made during various ecological studies, and the paper represents the south-east migration of the species towards lower latitudes. Such observations on the migration of the species may help in further designing the conservation management plan of the species as well as the landscape.